Orientalist Discourse In Najib Mahfouzh’s Short Story Finjanu-Shay, Analysis Of Orientalism by Edward W. Said: Wacana Orientalis Dalam Cerpen Finjanu-Shay Karya Najib Mahfouzh Analisis Orientalisme Edward W. Said - Al Farahil A'la Rahil (Pusaka Cendekia Indonesia Foundation, 2025)
Postcolonial discourse not only discusses the colonial past, but also examines how colonial heritage continues to shape the perspective and culture of people in former colonial countries. This study examines how traces of colonialism are present in literary works through the analysis of the short story Finjanu-Shay by Naguib Mahfouz. Using Edward Said's theory of orientalism as a theoretical foundation, this study uncovers how Western ideologies and values, such as capitalism and socialism, are represented as the standard of civilization, while the East is portrayed as inferior and backward. Through character symbolization and narrative metaphors, Mahfouz criticizes the dominance of Western culture that has been internalized in Eastern society. The results of the study show that today's colonialism no longer takes place through physical colonialism, but through cultural discourse and hegemony that continues to live in the postcolonial world order. Diskursus pascakolonial tidak hanya membahas masa lalu kolonial, tetapi juga mengkaji bagaimana warisan kolonial terus membentuk cara pandang dan budaya masyarakat di negara-negara bekas jajahan. Penelitian ini mengkaji bagaimana jejak kolonialisme hadir dalam karya sastra melalui analisis cerpen Finjanu-Shay karya Naguib Mahfouz. Dengan menggunakan teori orientalisme dari Edward Said sebagai landasan teoritis, penelitian ini mengungkap bagaimana ideologi dan nilai-nilai Barat, seperti kapitalisme dan sosialisme, direpresentasikan sebagai standar peradaban, sementara Timur digambarkan sebagai inferior dan tertinggal. Melalui simbolisasi tokoh dan metafora naratif, Mahfouz mengkritik dominasi budaya Barat yang telah terinternalisasi dalam masyarakat Timur. Hasil penelitian menunjukkan bahwa kolonialisme masa kini tidak lagi berlangsung melalui penjajahan fisik, tetapi melalui wacana dan hegemoni budaya yang terus hidup dalam tatanan dunia pascakolonial